Electroencephalogram and clinical manifestations of Rett syndrome in children - E S Herini; I Mangunatmadja; Purboyo S; Hardiono D Pusponegoro; Sunartini Sunartini (Indonesian Pediatric Society, 2003)
Background Rett Syndrome (RS) is a severe neurodevelopmentaldisorder. Epileptic seizures occur in 80-90%; grandmal, psychomo-tor (complex partial), and focal motor seizures have been reported.The electroencephalogram(EEG) is almost always abnormal.Objective This study aimed to investigate the EEG and clinicalmanifestations of children with RSResults We investigated EEG on 5 patients with RS aged 30–66month. One patient was in clinical stage II and 4 patients in clini-cal stage III. Four patients had history of seizures, however onlytwo patients suffered from epilepsy. The EEG demonstrated slow-ing background activity in occipital region in two patients. In addi-tion, epileptic form activities were observed in 4 of 5 patients.Conclusion We concluded that epileptic spike discharge with orwithout clinical seizures were found in almost all of our RS pa-tients. These paroxysmal discharges suggested the process andthe sequences of cortical involvement. Compelling clinical, neuro-physiological evidences were very important to decide the stageof Rett disorder